Pengalaman Keluarga dalam Merawat Penderita Gangguan Jiwa yang Menjalani Pengobatan di Bukittinggi: Hermeneutic Phenomenology Study : Family Experiences in Caring for Patients with Mental Disorders who Undergoing Treatment in Bukittinggi: Hermeneutic Phenomenology Study - Del Fatma Wati; Muhamad Arsyad Subu; Nedtrida (Fakultas Keperawatan Universitas Andalas, 2018)
Mental disorder is one of the diseases whose prevalence is increasing every year. From sufferers of mental disorders, relapses of mental patients are caused by lack of adherence to treatment, lack of family support and living conditions that are vulnerable to increased stress and pressure. The patient's family stated that they needed a large fee for medical treatment so they were not routinely go to the RSAM psychiatric clinic. The purpose of this study was to describe the family experience in treating mental disorders that underwent treatment in Bukittinggi. The design of this study uses qualitative methods with the Study Hermeneutical Phenomenology approach. The number of participants of 8 people was taken by purposive technique according to the research criteria. Methods of data collection in this study were in-depth interviews, and field notes. Phases in hermaneutic phenomenology study data analysis: reading interviews, summarizing coding, analyzing transcripts, returning to participant texts, comparing and distinguishing, identifying patterns, integrating themes. This research produces two themes (1) Alternative Medicine (2) Economic Expenses. The results of this study can be a reference especially for families in caring for people with mental disorders in order to increase support for patients with mental disorders in caring so that they can be independent at home.